Sustainable Finance in Africa: A Comparative Overview - Gebreysus Abegaz Yimer (Mizan law review, 2024)
The international community has introduced many policies and strategies to transform the economy into a green and sustainable economy. As finance is the economy's lifeblood, reform in the financial sector is vital to achieving sustainable development. The financial industry has two main aims in promoting sustainable finance. To protect itself from risks that emanate from the climate crisis and to positively contribute to transforming the economy into a green and sustainable economy. Some African countries have introduced legal and policy frameworks to reorient the financial industry into a more sustainable path. This article examines the experience of five African countries: South Africa, Nigeria, Ghana, Kenya and Ethiopia. African banks and financial institutions voluntarily join international initiatives and adapt to international standards. This shows that the industry is open to embracing the inevitable change that determines the future of finance in domestic and international markets. African countries are also taking essential steps with a growing interest in doing more. African countries can benefit from the new trends in the financial market. However, lack of resources, proper policy and legal frameworks, and lack of qualified experts are still challenging the transformation to sustainable finance in Africa. The African Union is thus expected to coordinate the efforts of individual countries to transform the continent's financial sector into a more sustainable path. So far, only a few AU initiatives concerning sustainable finance exist.